Anastasia - Cusack, John; Ryan, Meg (Beverly Hills, CA 20th Century Fox Home Entertainment, 2006)
Princess Anastasia has been missing ever since the Russian revolution. Now she's living on the streets, and Vladimir is trying to convince her to claim a reward. This new edition features new extras including Anastasia's Music Box Favorites
Originally released as a motion picture in 1997
Special features: Interactive feature lets viewer draw all the main characters; "The making of 'Anastasia'" exclusive featurette; sing-alongs & lessons in how to sing in another language; 3-D walk through the Palace; fun & creative set-top games
Title from container
2
Keywords: Animated films; Children's films; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs